A new species of Mandevilla (Apocynaceae; Apocynoideae) from Mexico - Alvarado-Cárdenas, Leonardo O.; Lozada-Pérez, Lucio (Phytotaxa, 2017)
We describe and illustrate a new species of Mandevilla for the states of Oaxaca and Veracruz, Mexico. Mandevilla sherlockii sp. nov. can be separated from the other similar species of the genus by its subcoriaceous leaf blades and inflorescences with a conspicuously curved rachis between each flower. Including this new species, Mexico is a hotspot for the genus with a 24 species, 11 of which are endemic. We provide a distribution map, suggest a conservation status for the new species, and provide a key for the species of Mandevilla found in Mexico and Central America.